2017
DOI: 10.1371/journal.pone.0169994
|View full text |Cite
|
Sign up to set email alerts
|

Rare Synaptogenesis-Impairing Mutations in SLITRK5 Are Associated with Obsessive Compulsive Disorder

Abstract: Obsessive compulsive disorder (OCD) is substantially heritable, but few molecular genetic risk factors have been identified. Knockout mice lacking SLIT and NTRK-Like Family, Member 5 (SLITRK5) display OCD-like phenotypes including serotonin reuptake inhibitor-sensitive pathologic grooming, and corticostriatal dysfunction. Thus, mutations that impair SLITRK5 function may contribute to the genetic risk for OCD. We re-sequenced the protein-coding sequence of the human SLITRK5 gene (SLITRK5) in three hundred and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…Slitrk proteins, members of the Slit and Trk-like (Slitrk) protein family, are type I transmembrane leucine-rich repeat (LRR) domain-containing proteins that are broadly expressed in the central nervous system and enriched at synapses. Interestingly, mutations in Slitrk genes have been associated with neuropsychiatric disorders (Abelson et al, 2005;Zuchner et al, 2006;Proenca et al, 2011;Piton et al, 2011;Shmelkov et al, 2010;Song et al, 2017;Cavani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Slitrk proteins, members of the Slit and Trk-like (Slitrk) protein family, are type I transmembrane leucine-rich repeat (LRR) domain-containing proteins that are broadly expressed in the central nervous system and enriched at synapses. Interestingly, mutations in Slitrk genes have been associated with neuropsychiatric disorders (Abelson et al, 2005;Zuchner et al, 2006;Proenca et al, 2011;Piton et al, 2011;Shmelkov et al, 2010;Song et al, 2017;Cavani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Both SAPAP3 and Sltirk5 KO mice, which exhibit a high degree of OCD-like grooming behavior and anxiety-like behaviors, are considered relevant models for the corresponding human conditions, such as OCD. In fact, mutations in Sltirk5 and SAPAP3 have been linked to increased risk of OCD in humans 36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Slitrk5 KO mice display OCD-like behavior, as they present with severe facial lesions associated with excessive grooming 55 . In relation to this, it has also been shown that rare functional mutations in SLITRK5 contribute to the genetic risk for OCD in humans 75 . SALM1 KO mice, on the other hand, exhibit autism-like behavioral abnormalities, such as social withdrawal and increased stereotyped activities 54 .…”
Section: Lrr Proteins In Behavior and Neurological Diseasementioning
confidence: 95%